Energetic Efficiency of an Existing Waste to Energy Power Plant. (November 2016) - Di Maria, Francesco; Contini, Stefano; Bidini, Gianni; Boncompagni, Antonio; Lasagni, Marzio; Sisani, Federico
Abstract: The energetic efficiency (EE) of an existing waste to energy plant (WtE) was investigated in the perspective of the waste framework directive 2008/98/EC (WFD). WFD introduced the possibility of considering the WtE a material recovery facility if its EE resulted not lower than 0.6. Currently the analyzed WtE recovers only electrical energy from waste combustion by a steam turbine and showed an EE of about 0.44. This figure can be increased up to 0.6 if the WtE is operated in a combined heat and power mode (CHP). CHP can be realized exploiting a given fraction of the saturated steam generated by the evaporator. In the average operating conditions of the WtE about 2, 900 kg/h of steam used for CHP can lead to EE ≥ 0.6. This heat was used for feed and organic Rankyne cycle able to produce up to 250 kW with an average electrical efficiency of about 13%, comparable to the one of the WtE.